'Voice' and 'Choice' in Modern Working Practices: Problems With the Taylor Review. (29th January 2018) - Bales, Katie; Bogg, Alan; Novitz, Tonia
Abstract: In July 2017, the Taylor Review on 'Modern Working Practices' was published. Led by Matthew Taylor, the Review aimed to consider the implications of new emerging business models for both worker rights and employer obligations. Its recommendations seem ill-informed, methodologically unsound and, ultimately, unlikely to address the widespread deprivation of workers' rights within the 'gig' economy and contemporary workplace. We shape our critique of the Taylor approach by reference to the constructions of 'choice' used in the Review and the limited scope permitted for worker 'voice'. In particular, we observe an evasion of international labour standards relevant to 'decent work' and a lack of attention to fundamental human rights. Identifying methodological flaws in the Report and focusing on three central areas of reform: employment status; zero-hours contracts (ZHCs); and workers' voice and representation, this article critically analyses a number of the proposals put forward, concluding that many of the Taylor Review recommendations are not only problematic, but dangerous, with potentially serious deregulatory repercussions for UK workers if actioned upon and implemented by the current Government.